The Oil Fields Relation to the Tectonic Boundaries that inferred from Seismic and Gravity Interpretation in Kut-Hai-Fajir and Surrounding Area, Central Iraq - S. AL-Banna1, Ahmed; A.M.AL-Zubaidi, Ali; M. Daim, Falih (Iraqi Journal of Science, 2021)
The seismic reflection and gravity data were used to detect the tectonic boundaries in Kut-Hai-Fajir and surrounding areas, central Iraq. The depth maps of Dammam, Nhr Umr, and Sulaiy, formations were constructed and used to detect some boundareis in the study area. The residual gravity map and Total Horizantal derivative (THDR) also used to detected the tectonic boundaries. It is obtained that most boundaries or faults found in the deep formations; while some of them showen in the shallow fomations. The faults or boundaries obtained from gravity intrpretation mostly coincied with the deepest formation boundaries. Generally, the grvity anomalies conform the morphological feature locations within the depth maps of the formations. Many longitudinal and transverse faults were traced from the seismic and gravity interpretation. It is concluded that the oil fields in the study area lying within certain tectonic zones and coincide with the positive residual gervity anomalies of spacing window of 8 km; mostly near the zero line values. It is believed that the integrated interpretation of residual gravity anomalies with the depth maps of some formations, that inferred from seismic data, gives good results for evaluation of an area for oil exploration.